USING CHILDREN SHORT STORIES TO DEVELOP STUDENTS’ READING COMPREHENSION ON NARRATIVE TEXT - Putri Utami Sundari; Wahid Hasyim (EEAL Journal (English Education and Applied Linguistics Journal), 2020)
This research is aimed to find out whether there is any significant improvement of using short stories method in students’ reading comprehension on narrative text. The participants for this research were one class consisting of thirty two students from the second grade of a junior high school in West Java. This research implemented pre-experimental design as research method. The data were obtained from the tests involving pre-test and post-test in order to know the students’ reading comprehension on narrative text before and after using short stories method. Type of the tests used was multiple choices in which every test consisted of twenty questions. The result of the instruments was analyzed quantitatively using statistical analysis. It can be seen in the result of the hypothesis testing through T-Test formula in the significance degree (α) = 0.05. The result showed that tobserved = 18.198 ≥ tcritical = 2.0395. Therefore the null hypothesis (Ho) of this research is rejected and alternative hypothesis (Ha) of this research is accepted. Then, the normalized gain of this research is categorized as medium with average value 0.45. Based on the result, it could be concluded that using short stories method has significant improvement to develop students’ reading comprehension on narrative text.